Малий бізнес в аграрному підприємництві та особливості класифікації його суб’єктів - Яворська, Тетяна Іванівна; Яворская, Татьяна Ивановна; Yavorska, Tetiana (My University, 2016)
Розглянуто законодавче визначення суб’єктів малого, середнього та великого підприємництва в Україні. Проведене групування сільськогосподарських підприємств і фермерських господарств за середньообліковою чисельністю працюючих та виручкою від реалізації продукції. Рекомендована класифікація суб’єктів малого бізнесу із врахуванням розміру земельної площі. Визначена роль господарств населення у розвитку аграрного підприємництва та їх перспективи щодо включення у склад суб’єктів малого бізнесу.Setting objectives. Matching the size of a small business with its legal definition in agriculture Ukraine considers most businesses to small. This agricultural statistics use other approaches to the definition of small business. Subsidiary farm commodity focus never included in the subjects of small business. Research results. Legislative definition of micro, small, a medium and large enterprise in Ukraine is considered. The calculation of their share in the total number of undertakings in agriculture made. Grouping of farms and farms for the average number of employees and revenue from sales made. Among the farms to small business concerns - 75.9% of medium enterprises - 21.2% of large businesses - 2.9%. Grouping by proceeds from the sale of products for the current euro exchange rate of the UAH (about 27-28 UAH per 1 euro) will carry almost all businesses in agriculture to small businesses. Conclusions. The feasibility of changing the approach to establishing small businesses in agriculture, taking into account the specifics of the industry and the diversity of forms of management is available. Classification of small businesses, taking into account criteria such as the size of the main land area is recommended. The role of households in the development of agricultural entrepreneurship is defined. Prospects for households to include in the composition of small business are deals.
Keywords: аграрне підприємництво; малий бізнес; суб’єкти підприємництва; особисті селянські господарства; фермерські господарства; сільськогосподарські підприємства; agricultural entrepreneurship; small business; business entities; private farms; farms; agricultural enterprises